Marketing Strategy Study of Marvel Studios’ Marvel Cinematic Universe - Ma, Jie (Transactions on Economics, Business and Management Research, 2024)
This paper aims to comprehensively analyze the marketing strategies employed by Marvel Studios and propose actionable recommendations for enhancement. By conducting an in-depth examination of the key elements of Marvel’s marketing approach, including teasers, social promotions, storytelling, and the launch of new episodic projects, this study identifies several strengths in the studio’s marketing endeavors. While Marvel Studios has demonstrated prowess in various aspects of marketing, such as engaging teasers and effective social promotions, it has also faced significant challenges, particularly in its social media campaigns in China, the introduction of film and television productions into the Chinese market, and the maintenance of production quality. To address these challenges, this paper proposes a set of recommendations aimed at improving the efficacy of Marvel’s social media operations in China, prioritizing the introduction of film and television works in the Chinese market and maintaining a strong focus on the quality of its productions. Implementing these recommendations is expected to enable Marvel Studios to expand its presence in the Chinese market further, enhance its brand value, and foster long-term development. This study holds considerable reference value not only for Marvel Studios but also for the broader film and television industry. By offering practical suggestions and guidance tailored to the Chinese market, this paper contributes to the advancement and growth of related companies operating in this dynamic and rapidly evolving landscape.